The Influence of Career Development and Work Placement on Employee Performance in The Department Public Work in The City of Solok - Delfi Sartika; Netti Indrawati; Esi Sriyanti (Cita konsultindo, 2022)
Based on observations made, the basis for career development for an employee includes promotions carried out by the leadership in each section, education possessed by employees. Work Placement where the leadership more often prioritizes employees who have a higher level of education (Bachelor or Postgraduate) compared to employees who are still educated in high school to occupy positions such as head of section or head of sub-section of each section. The purpose of the study was to determine the effect of career development and work placement on employee performance at the Public Works Department of Solok City.This research was conducted at the Solok City Public Works Office, which is located at Denpal Junction, Solok City. This type of research uses a descriptive quantitative approach. The sources of data used in this study are primarily through the distribution of questionnaires regarding career development and job placement that have a positive effect on employee performance. The sampling technique was carried out by total sampling, as many as 85 people.The results show that partially career development has a positive effect on employee performance, the t-count value is greater than the t-table, namely 4.062 > 1.1988, and the significant value is 0.000 <0.05 and work placement has a positive effect on employee performance . t table is 3.043 > 1.1988 and the value is not significant 0.000 <0.05. Based on the F test, the Fcount value is 17.895 and the Ftable value is 3.11. This states that simultaneously or simultaneously career development and work placement have a positive effect on employee performance at the Solok City Public Works Office.